DIAGNOSTICS, TREATMENT AND PREVENTION OF CANINE PARVOVIRUS ENTERITIS IN THE CLINIC “VETERINARY VIP-SERVICE” IN THE CITY OF POLTAVA - Titarenko О. V.; Pokhylets, K. S.; Karasenko, A. Yu. (Scientific Progress & Innovations, 2021)
The results of researching diagnostics, treatment and prevention of canine parvovirus enteritis in the city of Poltava have been presented. 338 dogs suffering from parvovirus enteritis were registered in the clinic “Veterinary VIP-service” of Poltava during the period of 2016–2018. The diagnosis of parvovirus enteritis was established in the complex taking into account epizootological data, anamnesis data, and clinical signs. Immune chromatographic express tests based on detecting the pathogen antigen were performed to confirm the diagnosis. During 2019, 105 dogs with parvovirus enteritis were detected in the clinic. The disease epizootic process was characterized by seasonality. Thus, the highest disease intensity was observed in autumn – 36.2 %, and the lowest (16.3 %) – in the winter period. Animals, which fell ill, had not been vaccinated against parvovirus enteritis, or the correct vaccination schedule had not been followed. Most patients with canine parvovirus enteritis were among puppies aged 2–4 months, which made 62.9 % of all diseased animals. Such dog breeds as Yorkshire Terrier, Maltese Lap-dog, Toy Terrier, German Shepherd, and non-pedigree dogs fell ill more often. High effectiveness of the used vaccines Nobivak ChGPPI, Duramun Plus 5 L4, Wangard Plus 5/L, and Eurican ChGPPI2-L for the prevention of parvovirus enteritis in 768 dogs in “Veterinary VIP-service” clinic has been confirmed. A new treatment scheme proposed by us, in contrast to the basic scheme, included the application of another antiemetic preparation Serenia, antispasmodic NO-SPA, hemostatic medicine Contriven, immune-modulating preparation Anfluron and antibiotic Farmazin-50, and also additionally specific hyper-immune serum Giskan-5, sulfanilamide Brovaseptol preparation for injections and probiotics with prebiotics Dolvit Probiotic to restore the intestinal microbiome. It has been clarified that the application of the new treatment scheme proposed by us was more effective than the basic scheme not only because of the speed of animals’ recovery, but also for the absence of lethal cases.